Influence Of Health Preventive Behavior On HIV/AIDS : Literature Review - Irwansyah, Silvana Lestari; Hilmi, Indah Laily; Salman, Salman (Jurnal EduHealth, 2022)
HIV (Human Immunodeficiency Virus) is a major problem in many countries, including Indonesia. Preventive behavior towards HIV/AIDS must be accompanied by the implementation of appropriate health policy strategies in each country. Objective: to identify the behavior of HIV/AIDS prevention in Indonesian society. Method: literature study by choosing a topic, finding keywords, and making a journal review. Search through Google Scholar and scientific journals published nationally and internationally in the last 10 years, namely 2012 – 2022. Result: improvement in health services is needed such as HIV/AIDS counseling, peer education, VCT, and other innovative programs. Conclusion: it is necessary to strengthen community behavior to improve health status in order to prevent HIV from occurring in at-risk groups.